(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article discusses gender issues and the formation of feminist movements at different stages of social development. The article also analyzes the specific scientific approaches of philosophers of different periods to the problem of gender equality. It also provides a socio-philosophical analysis of the solution of these issues by advancing the social status of women in modern society.